PENERAPAN MODEL COOPERATIVE LEARNING TIPE JIGSAW UNTUK MENINGKATKAN PEMAHAMAN SISWA TERHADAP SEJARAH PERKEMBANGAN ISLAM DI SMP IT SALMAN BIN ASWET NU - Salman Salman; Nirwaina Pohan Nirwaina Pohan (lembaga Sepercenter, 2024)
This study aims to analyze the effectiveness of the application of the Jigsaw type Cooperative Learning model in improving students' understanding of the subject of History of Islamic Development at IT Salman Bin Aswet NU Middle School. The research method used is Classroom Action Research (CAR) with a qualitative and quantitative approach. The subjects of this study were eighth grade students who had difficulty understanding history material. The results showed that the application of the Jigsaw model was able to significantly improve students' understanding. This is proven by the increase in the average grade from pre-cycle to cycles I and II. In addition, this model also increases students' active involvement in learning, strengthens social interaction, and improves their critical thinking skills. Thus, the Jigsaw-type Cooperative Learning model can be an effective alternative learning strategy to improve students' understanding of the history of Islamic development.